The Role of Handouts in Development of English in ESL Classes (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The implementation of handouts in the classroom is crucial, and creating them takes time, creativity, and skill from the teacher. In this article highlights the role of handouts in the development of English in ESL (English as a Second Language) classes. They can considerably aid in the process of acquiring a language and are valuable resources for language learners.